Management plans and their impact on school improvement - Polo Martínez, Ignacio; Puertas Bescós, Gemma (Avances en Supervisión Educativa, 2016)
OECD (2015) states that management’s leadership is a critical factor for implementing reforms and improving schools. Candidates are required to submit a management plan outlining the framework of a plan to be followed during their 4 year term. Despite the plan outlined in the proposal, the implicit "non aggression pact" between the participants (the teachers and the directors, who are teachers themselves), makes change difficult. As a result, management plans have little impact on improving methods of teaching and academic results achieved by the students. In this article we have tried to achieve three objectives: 1) analyze the relationship between the renewal, selection and appointment of a director with the management plan around our country, 2) analyze which aspects are those that, according to major international studies, should determine the content, development and evaluation of a management plan, and 3) to suggest how one could implement a management plan for an education center or school.